2019
DOI: 10.1159/000496637
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Itching in Patients with End-Stage Renal Disease: Treatment with Nalfurafine Hydrochloride

Abstract: Background/Aims: In this study, we investigated the severity and frequency of uremic pruritus and itch-associated insomnia in patients with end-stage renal disease (ESRD) or chronic kidney disease (CKD). Methods: This questionnaire-based study included outpatients with ESRD or CKD who were attending Tokorozawa Renal Clinic in Saitama Prefecture or Musashi Ranzan Hospital and were stable on treatment. The questionnaire was completed by patients on hemodialysis (HD) before a dialysis session and by patients on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…This notwithstanding, another study showed a lack of significant difference in severity of itching and similar prevalence of CI in HD and PD patients (61.8% and 61.5%, respectively). 19 The research also investigated pruritus in a group of patients with stage 4 or 5 CKD without dialysis therapy, where the prevalence of CI was 43.2%. Another cross-sectional study determined the prevalence of CI in a group of 3,780 non-dialysis patients with CKD stages 3-5.…”
Section: Prevalencementioning
confidence: 99%
“…This notwithstanding, another study showed a lack of significant difference in severity of itching and similar prevalence of CI in HD and PD patients (61.8% and 61.5%, respectively). 19 The research also investigated pruritus in a group of patients with stage 4 or 5 CKD without dialysis therapy, where the prevalence of CI was 43.2%. Another cross-sectional study determined the prevalence of CI in a group of 3,780 non-dialysis patients with CKD stages 3-5.…”
Section: Prevalencementioning
confidence: 99%
“…Several therapeutic approaches have been tried, with varying degrees of success. These include topical approaches, with ointments and phototherapy, massage, essential oils or, more recently, Chinese herbal-bath therapy and acupuncture [3,[13][14][15][16][17][18][19]. A vast array of systemic treatments has also been essayed, including μ-opioid receptor antagonists and κ-agonists, anti-inflammatory and antihistamine medications, and gabapentin, one of the most widely studied drugs, and, possibly also for this reason, the only one associated with a significant improvement in a recent meta-analysis.…”
Section: Pruritus In Ckd-eskdmentioning
confidence: 99%
“…In Japan, nalfurafine hydrochloride (NAL) was launched in 2009; its indication is for 'improvement of pruritus in dialysis patients (only for cases resistant to conventional treatments)' [8,9]. However, the degree of improvement in pruritus in patients receiving NAL has varied considerably [10][11][12].…”
Section: Introductionmentioning
confidence: 99%